2017
DOI: 10.1038/onc.2017.261
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of colony stimulating factor-1 receptor abrogates microenvironment-mediated therapeutic resistance in gliomas

Abstract: Glioblastomas represent the most aggressive glioma grade and are associated with a poor patient prognosis. The current standard of care, consisting of surgery, radiation and chemotherapy, only results in a median survival of 14 months, underscoring the importance of developing effective new therapeutic strategies. Among the challenges in treating glioblastomas are primary resistance and the rapid emergence of recurrent disease, which can result from tumor cell-intrinsic mechanisms in addition to tumor microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
151
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(159 citation statements)
references
References 37 publications
6
151
1
1
Order By: Relevance
“…Many small molecules and antibodies were developed against CSF1R, and numerous clinical trials have been completed or are ongoing ( Table 3). PLX3397 is a small molecule targeting CSF1R, it reduced the number of TAMs in a preclinical GB model and showed an antitumor activity (Coniglio and Segall, 2013;Yan et al, 2017). In clinical studies, PLX3397 was also well tolerated and showed anti-tumor responses after treatment (Tap et al, 2015) (NCT01004861).…”
Section: Depletion Of Tamsmentioning
confidence: 99%
“…Many small molecules and antibodies were developed against CSF1R, and numerous clinical trials have been completed or are ongoing ( Table 3). PLX3397 is a small molecule targeting CSF1R, it reduced the number of TAMs in a preclinical GB model and showed an antitumor activity (Coniglio and Segall, 2013;Yan et al, 2017). In clinical studies, PLX3397 was also well tolerated and showed anti-tumor responses after treatment (Tap et al, 2015) (NCT01004861).…”
Section: Depletion Of Tamsmentioning
confidence: 99%
“…For example, patients with pilocytic astrocytoma (Grade I) had a five‐year survival rate of 94.4%, much higher than 4.7%, the five‐year survival rate of patients with glioblastoma multiforme (GBM, Grade IV) . Despite therapeutic advances in surgery, radiation, and pharmacotherapy, the median survival for GBM patients is only 14 months . With the identification of specific genetic mutations as “driver factors” of gliomagenesis, molecular parameters have been introduced to refine the diagnosis of gliomas such as IDH mutation, 1p/19q codeletion, and H3 K27M mutation, along with pathological parameters .…”
Section: Introductionmentioning
confidence: 99%
“…Several host cells have been shown to contribute to important features of cancer through several mechanisms. In GBMs, macrophages and microglia, astrocytes, and cells of the perivascular niche have been described to actively participate in the development of this disease through modulation of for example migration, invasion, angiogenesis, and therapeutic resistance (Calabrese et al, 2007;Charles, Holland, Gilbertson, Glass, & Kettenmann, 2012;Plate, Breier, Weich, & Risau, 1992;Pyonteck et al, 2013;Quail et al, 2016;Yan et al, 2017;Zhou et al, 2017).…”
mentioning
confidence: 99%